Predictive value of the KELIM in neoadjuvant treatment for patients with advanced ovarian cancer - Wang, Yicong; Yu, Yongai; Yuan, He; Wang, Lei; Bian, Pengfei; Yang, Yiming; Wang, Jiao (Frontiers in Oncology, 2026)
ObjectiveTo explore the significance of modeled CA-125 elimination rate constant (KELIM) in predicting satisfactory cytoreduction at interval debulking surgery (IDS), survival prognosis, and platinum-based chemosensitivity in patients with advanced ovarian cancer treated with neoadjuvant chemotherapy followed by interval debulking surgery (NACT-IDS).MethodsThe clinical information and follow-up data of 70 patients with advanced ovarian cancer who underwent NACT-IDS in the Department of Gynecology of Dalian Central Hospital from January 2010 to June 2023 were retrospectively analyzed. The KELIM for each patient during neoadjuvant chemotherapy was calculated using the online calculation tool (https://www.biomarker-kinetics.org/CA-125-neo), and its predictive value for IDS surgical outcome, prognosis, and platinum-resistant recurrence (PRR) was analyzed.ResultsA total of 70 patients met the inclusion criteria. The median follow-up time was 32 (range 6–116) months. KELIM was an independent factor for predicting satisfactory debulking at IDS. Patients with higher KELIM had a higher probability of achieving satisfactory debulking (1.40 vs. 0.61, P < 0.05). KELIM and IDS surgical outcomes were independent influencing factors for progression-free survival (PFS) and overall survival (OS). The median PFS and OS in patients with KELIM ≥1 were significantly higher than those in patients with KELIM <1 (26 months vs. 18 months, P < 0.05; 39 vs. 28 months, P < 0.05). KELIM ≥1 is an independent protective factor for subsequent recurrence of platinum resistance in patients with NACT-IDS. The median KELIM value of the platinum-sensitive recurrent group was significantly higher than that of the PRR group (1.30 vs. 0.73, P < 0.05). For patients with high KELIM, the risk of PRR is low even if IDS cytoreductive surgery is not satisfactory.ConclusionsKELIM is an important parameter to consider when performing IDS. The KELIM and IDS outcomes are independent predictors of the prognosis and PRR risk of patients with NACT-IDS. Even if cytoreduction is unsatisfactory, patients with high KELIM still have a lower risk of subsequent recurrence of platinum resistance.